Proposed Business Models for University Technology Commercialization: Insights from PT Rekacipta Inovasi, Institut Teknologi Bandung - Uruqul Nadhif Dzakiy (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
The current commercialization business model in universities emphasizes the role of the Technology Transfer Office (TTO) with its main activities in licensing and incubators with university spin-off incubation activities. Few studies have highlighted a business model in the form of a university profit-oriented company that focuses specifically on accommodating technology commercialization activities, especially in the Indonesian context. This study constructed technology commercialization business models from PT Rekacipta Inovasi, Institut Teknologi Bandung (PT RII). We conducted interviews with eight informants who are company’s management and staff, university’s management, and technology inventors. Using abductive approach, we found that business models for university technology commercialization are not only includes licensing practices and establishment of spin-off companies that focus on the Business to Business (B to B) market, but also joint venture and joint operation practices and direct selling with the Business to Costumer (B to C) market. Through this business model, universities can direct the commercialization practice of research results towards business practices that can generate revenue. This research provided a novel commercialization model for developing countries context which can be a reference for universities in carrying out their technology commercialization activities.